Proceedings of the 3rd International Conference on Knowledge Capture 2005
DOI: 10.1145/1088622.1088649
|View full text |Cite
|
Sign up to set email alerts
|

Automated story capture from conversational speech

Abstract: While storytelling has long been recognized as an important part of effective knowledge management in organizations, knowledge management technologies have generally not distinguished between stories and other types of discourse. In this paper we describe a new type of technological support for storytelling that involves automatically capturing the stories that people tell to each other in conversations. We describe our first attempt at constructing an automated story extraction system using statistical text c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Gordon investigated the problem of detecting stories in conversational speech [7] and weblogs [8] and [9]. In [7], the authors train a Naive Bayes classifier to categorize the transcribed text of a speech into story and non-story categories.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Gordon investigated the problem of detecting stories in conversational speech [7] and weblogs [8] and [9]. In [7], the authors train a Naive Bayes classifier to categorize the transcribed text of a speech into story and non-story categories.…”
Section: Related Workmentioning
confidence: 99%
“…In [7], the authors train a Naive Bayes classifier to categorize the transcribed text of a speech into story and non-story categories. Using word-level unigram and bigram frequency counts as feature vectors, they reported results for the classification of a speech as a story with 53.0% precision, 62.9% recall and 0.575 F-measure.…”
Section: Related Workmentioning
confidence: 99%
“…To automatically identify stories in the ICWSM corpus we followed a similar approach to Gordon & Ganesan [8], which takes a binary classification approach to the problem. However, in our work, entire blog posts are labeled as a positive or negative instance of a personal story, as opposed to extracting smaller segments from the text.…”
Section: The Case Library Story Corpusmentioning
confidence: 99%
“…There were an estimated 70 million weblogs in March 2007 (http://www.technorati.com), each with a series of entries containing the thoughts and ramblings of some computer user. We analyzed the entries of a random sample of 100 weblogs (approximately 12,000 sentences or 200,000 words) and found that 17% of weblog text consisted of stories, using the annotations guidelines of previous research [1]. By extrapolation, we can estimate that there are 23.8 billion words of story text available on the web for use in knowledge management and training applications.…”
Section: Stories In Internet Weblogsmentioning
confidence: 99%
“…Gordon & Ganesan [1] first demonstrated the feasibility of automatically extracting stories from text using statistical natural language processing techniques. The aim of their work was to develop technologies for identifying stories in conversational speech data, e.g.…”
Section: Statistical Story Extractionmentioning
confidence: 99%